2014
DOI: 10.1016/j.toxrep.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte osmotic fragility and lipid peroxidation following chronic co-exposure of rats to chlorpyrifos and deltamethrin, and the beneficial effect of alpha-lipoic acid

Abstract: The present study aimed to evaluate the effect of chronic co-exposure to chlorpyrifos (CPF) and deltamethrin (DLT) on erythrocyte osmotic fragility, lipid peroxidation and the ameliorative effect of alpha-lipoic acid (ALA) on erythrocyte fragility. Thirty-six male Wistar rats divided into six groups of six rats each were used for the study. Groups I (S/oil) and II (ALA) were given soya oil (2 ml/kg) and ALA (60 mg/kg), respectively. Rats in group III (DLT) and IV (CPF) were exposed to DLT (6.25 mg/kg) and CPF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…Human beings and animals are often exposed to mixtures of environmental contaminants including pesticides and metals [[31], [32], [33]]. Earlier investigations demonstrated that exposure to pesticides including fipronil, chlorpyrifos and deltamethrin disrupted antioxidant defense system which consequently induced oxidative stress in experimental animals whereas the adverse effects were ameliorated by the administration of exogenous antioxidants [32,34]. However, continuous low-dose dietary exposure to pesticide α-cypermethrin reportedly did not induce liver damage, oxidative stress and impaired antioxidant defense in rats [35].…”
Section: Discussionmentioning
confidence: 99%
“…Human beings and animals are often exposed to mixtures of environmental contaminants including pesticides and metals [[31], [32], [33]]. Earlier investigations demonstrated that exposure to pesticides including fipronil, chlorpyrifos and deltamethrin disrupted antioxidant defense system which consequently induced oxidative stress in experimental animals whereas the adverse effects were ameliorated by the administration of exogenous antioxidants [32,34]. However, continuous low-dose dietary exposure to pesticide α-cypermethrin reportedly did not induce liver damage, oxidative stress and impaired antioxidant defense in rats [35].…”
Section: Discussionmentioning
confidence: 99%
“…It also interfered with glucose-6-phosphate dehydrogenase activity that are required for membrane integrity (Mayes, 1983;Champe et al, 2005;Ojo et al, 2006). Although erythrocytes are well equipped with several biological mechanisms to defend against intracellular oxidative stress (Prasanthi et al, 2005) they can be oxidatively damaged due to toxic chemicals and environmental pollutants (Uchendu et al, 2014). Another view of the mechanism of fragility is that the hydrocarbon component also interfered with the membrane sodium pump mechanism that maintains a low level of sodium ion concentration inside the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro [21,22] and in vivo [23,24] studies have demonstrated that chlorpyrifos exposure induces oxidative stress. Oxidative stress is known to activate redox sensitive kinases (RSKs) like NFκB (Nuclear Factor kappa B) and p38 MAPK (p38 Mitogen-Activated Protein Kinase) [25][26][27].…”
Section: Introductionmentioning
confidence: 99%